Differential Uptake of Telehealth for Prenatal Care in a Large New York City Academic Obstetrical Practice during the COVID-19 Pandemic - Limaye, Meghana A.; Lantigua-Martinez, Meralis; Trostle, Megan E.; Penfield, Christina A.; Conroy, Erin M.; Roman, Ashley S.; Mehta-Lee, Shilpi S. (American Journal of Perinatology, 2020)
During the coronavirus disease 2019 (COVID-19) pandemic in New York City, telehealth was rapidly implemented for obstetric patients. Though telehealth for prenatal care is safe and effective, significant concerns exist regarding equity in access among low-income populations. We performed a retrospective cohort study evaluating utilization of telehealth for prenatal care in a large academic practice in New York City, comparing women with public and private insurance. We found that patients with public insurance were less likely to have at least one telehealth visit than women with private insurance (60.9 vs. 87.3%, p < 0.001). After stratifying by borough, this difference remained significant in Brooklyn, one of the boroughs hardest hit by the pandemic. As COVID-19 continues to spread around the country, obstetric providers must work to ensure that all patients, particularly those with public insurance, have equal access to telehealth.Key Points
Keywords: prenatal care; COVID-19; telehealth; telemedicine; health care disparities